CON4EI: CONsortium for in vitro Eye Irritation testing strategy - EpiOcular™ time-to-toxicity (EpiOcular ET-50) protocols for hazard identification and labelling of eye irritating chemicals. (June 2018) - Kandarova, Helena; Letasiova, Silvia; Adriaens, Els; Guest, Robert; Willoughby, Jamin A.; Drzewiecka, Agnieszka; Gruszka, Katarzyna; Alépée, Nathalie; Verstraelen, Sandra; Van Rompay, An R.
Abstract: Assessment of acute eye irritation potential is part of the international regulatory requirements for testing of chemicals. The objective of the CON4EI (CONsortium for in vitro Eye Irritation testing strategy) project was to develop tiered testing strategies for eye irritation assessment for all drivers of classification. A set of 80 reference chemicals (38 liquids and 42 solids) was tested with eight different alternative methods. Here, the results obtained with reconstructed human cornea-like epithelium (RhCE) EpiOcular™ in the EpiOcular time-to-toxicity Tests (Neat and Dilution ET-50 protocols) are presented. The primary aim of this study was to evaluate whether test methods can discriminate chemicals not requiring classification for serious eye damage/eye irritancy (No Category) from chemicals requiring classification and labelling for Category 1 and Category 2. In addition, the predictive capacity in terms of in vivo drivers of classification was investigated. The chemicals were tested in two independent runs by MatTek In Vitro Life Science Laboratories. Results of this study demonstrate very high specificity of both test protocols. With the existing prediction models described in the SOPs, the specificity of the Neat and Dilution method was 87% and 100%, respectively. The Dilution method was able to correctly predicting 66% of GHS Cat 2 chemicals, however, prediction of GHS Cat 1 chemicals was only 47%–55% using the current protocols. In order to achieve optimal prediction for all three classes, a testing strategy was developed which combines the most predictive time-points of both protocols and for tests liquids and solids separately. Using this new testing strategy, the sensitivity for predicting GHS Cat 1 and GHS Cat 2 chemicals was 73% and 64%, respectively and the very high specificity of 97% was maintained. None of the Cat 1 chemicals was underpredicted as GHS No Category. Further combination of the EpiOcular time-to-toxicity protocols with other validated in vitro systems evaluated in this project, should enable significant reduction and even possible replacement of the animal tests for the final assessment of the irritation potential in all of the GHS classes. Highlights: A testing strategy, combining 2 time-to-toxicity protocols for eye irritation assessment was developed. The sensitivity for predicting GHS Cat 1 and GHS Cat 2 chemicals was 73% and 64%, respectively. Specificity of the 97% was achieved. None of the Cat 1 chemicals was underpredicted as GHS No Category.